The acute exercise response of peripheral blood mononuclear cells and their bioenergetic function in women with high and low systemic estradiol levels - Sira Karvinen; Emilia Lähteenmäki; Bettina Hutz; Hanna‐Kaarina Juppi; Jari E. Karppinen; Anna Kankaanpää; Maarit Lehti; Eija K. Laakkonen (Physiological Reports)
Abstract Decrease in the systemic estradiol (E2) levels caused by menopause has been associated with an increased risk for cardiovascular disease. We have previously shown that E2 level is associated with the systemic response to an acute bout of endurance exercise. However, the association of systemic E2 level with peripheral blood mononuclear cell (PBMC) bioenergetic function has not been investigated. We examined the associations of systemic E2 level (HIGH and LOW E2 groups) on WBC count and PBMC bioenergetic function before and after an acute bout of endurance exercise (time points PRE, POST and 1 h POST exercise). Exercise stimulus was a maximal incremental bicycle ergometer test. We show that an acute bout of exercise induced a transient increase in WBC count in both HIGH and LOW E2 study groups (p < 0.001). We also observed an increase in the percentage of neutrophils and a decrease in the percentage of lymphocytes in response to exercise (p < 0.001). An acute bout of exercise was also associated with a transient increase in PBMC maximal electron transfer capacity and spare capacity (p < 0.001). No statistically significant associations were observed between systemic E2 level and PBMC bioenergetic function at the basal state or in the responses to acute exercise.